A bibliometric analysis of papers published in the South East Asia Journal of Public Health from 2011 to 2015 - Majumder, Md Anwarul Azim; Rahman, Sayeeda; Rabbi, Ahbab Mohammad Fazle; Das, Palash (South East Asia Journal of Public Health, 2016)
South East Asia Journal of Public Health (SEAJPH) is a Bangladesh-origin, open access and peer reviewed international journal. This study conducted a bibliometric analysis of papers published in the SEAJPH from 2011 to 2015 using data extracted from the Bangladesh Journal Online database. Five volumes (which include eight issues) with a total of 108 papers were included in the analysis. The highest number of papers were published in 2012 and the average number of papers published per year was 21.6. More than 58% of published papers were original research, followed by short communications (12.96%).The highest proportion of papers were published during the study period by single authors (20.37%) or three authors (20.37%), followed by double authors (19.44%). he maximum of average authors/article was found to be 4 in the year 2011, and the minimum was 2.6 in the year 2015. The degree of collaboration in SEAJPH is approximately 0.80, and the collaboration was consistently high every year (ranges from 0.74 to 0.87). The maximum number of papers was published by professionals from India (35.16%), followed by Bangladesh (25%) and the UK (13.89%). Timely and accurate evidence-based information from health-related research/publications provide the extent and burden health problems/challenges of countries and regions. AS the SAARC region has the greatest total disease burden of any region in the world and relevant public health research and dissemination/collaboration of findings is crucial to alleviate this burden. The SEAJPH is successful in this regard. However, the journal needs indexing to popular search engines (e.g. PubMed) to attract global researchers and eventually lead to an increase in the citation of the papers. South East Asia Journal of Public Health Vol.5(1) 2015: 51-54